Estudo teórico das funções clássicas da pena à luz da psicanálise - Faiçal, Larissa Pizzotti (2021)
The functions of the penalty have been a topic debated for several decades by scholars of criminal law, criminology and other sciences interested in the subject. Nevertheless, the answers from the research that reprises the single use of the law has invariably offered answers from the past, which reside in absolute and relative theories, especially in the vindicative, retributive and intimidating function of the penalty. For this reason, and trying to expand the knowledge of these propositions, which are already so elaborated, the present work proposes an analysis of such functions of the penalty in the light of Freud’s psychoanalysis. Just as revenge is born in criminal law birth, the historical development re-elaborated by the psychoanalytic method of the return of the repressed allows the reading that new clothes were taking the place of the first punitive ritual and that the then father of the hour becomes the father State. The union of each of the treated theories and the psychoanalytic concepts enable a current reading of punishing, uniting society and complexity